First contact - Oxenburgh, Richard (Ethnographic video online, volume 1, 1983)
This is the classic film of cultural confrontation that is as compelling today as when it was first released over 20 years ago. When Columbus and Cortez ventured into the New World there was no camera to record the drama of this first encounter. But, in 1930, when the Leahy brothers penetrated the interior of New Guinea in search of gold, they carried a movie camera. Thus they captured on film their unexpected confrontation with thousands of Stone Age people who had no concept of human life beyond their valleys. This amazing footage forms the basis of First Contact. Yet there is more to this extraordinary film than the footage that was recovered. Fifty years later some of the participants are still alive and vividly recall their unique experience. The Papuans tell how they thought the white men were their ancestors, bleached by the sun and returned from the dead. They were amazed at the artifacts of 20th century life such as tin cans, phonographs and airplanes. When shown their younger, innocent selves in the found footage, they recall the darker side of their relationship with these mysterious beings with devastating weapons. Australian Dan Leahy describes his fear at being outnumbered by primitive looking people with whom he could not speak. He felt he had to dominate them for his own survival and to continue his quest for gold. First Contact is one of those rare films that holds an audience spellbound. Humor and pathos are combined in this classic story of colonialism, told by the people who were there.